Evolution of the body fat percentage of a professional soccer team over three seasons. (Spanish First Division``La Liga´´) - Del Valle Pascual, F.; Gomez Vera, G. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Nowadays, Soccer is the sport which has the most practitioners, besides a lot of supporters. Professional football clubs, which play in the biggest leagues and championships, count on an increasingly high budget. This has led to soccer players receiving the best medical care, aiming to maintain an appropriate health and performance status, among other aspects. To provide these services, it is necessary that doctors, fitness coaches, rehab fitness coaches, physiotherapists, psychologists and nutritionists work closely together. The multidisciplinary approach of all these specialists can bring the players towards success. At the beginning of the season, one of the factors to monitor is the nutritional assessment, where the body composition measure is. The body fat percentage is one of the factors to consider, since the references values in elite soccer players have proved a better performance and lower injury risks. For this reason, it is vitally important to know this percentage, in order to provide an ideal competition weight to the players.